Industry Payments by Allergan, Inc to Plastic Surgery and Related Specialties in 2018. Issue 1 (January 2021) - Isbester, Kelsey; Boas, Samuel; Summerville, Lesley; Wee, Corinne; Kumar, Anand
Abstract : Abstract: In 2014, payments to medical providers from drug/device manufacturers were made public through the Open Payments Database. Although previous studies have used the Open Payments Database to describe relationships between specialties and industry, few have evaluated specific companies and the effect of their contributions. As a large contributor to industry payments in plastic surgery, Allergan, Inc represents a significant source of potential financial conflicts of interest in the field. In this study, we aimed to describe the quantity, type, and specific products associated with Allergan's payments to both plastic surgeons and physicians of other specialties. In 2018, Allergan paid a total of 48, 484, 163 in 397, 225 payments to 90, 386 physicians. Psychiatry and neurology received 11, 867, 861 in payments, the largest of any specialty, whereas internal medicine received the largest number of individual payments. Plastic surgeons made the most per physician (3025). Most payments made to plastic surgeons were categorized as "gifts." Payments made in relation to Botox were predominantly made to neurologists, whereas most payments attributed to Natrelle breast implants were made to plastic surgeons (74.4%). Surprisingly, 18.2% of Natrelle payments were made to family medicine physicians. Further study is needed to fully understand the implications of the financial contributions revealed in this study.